Spinal muscular atrophy: a perspective outlook - M. R. Shaimurzin; I. S. Lutskiy (Кубанский научный медицинский вестник, 2020)
Background. Recent decades have witnessed a leap in understanding the molecular genetic bases of spinal muscular atrophy for a considerable improvement in diagnosis and treatment of this disease and development of innovative therapies for correcting genetic deﬁciencies. Given scarcity of etiotropic therapies for spinal muscular atrophy, traditional effective approaches remain relevant to target pathophysiological mechanisms of the disease progression and demand further development and improvement.Objectives. Efﬁcacy assessment of proactive therapy to spinal muscular atrophy based on electromyographic techniques using veriﬁable patient-speciﬁc functional scales.Methods. The study is designed as a prospective cohort study conducted at the Republican Clinical Centre for Neurorehabilitation. We used a 15-year monitoring data on 95 children (66 boys and 29 girls) with genetically conﬁrmed proximal spinal muscular atrophy. Patients were divided in two cohorts. The main cohort (65 children) received personalised therapy based on a proactive comprehensive stepwise approach to isolate a stem pathological pattern with clinical and electromyographic data. The comparison cohort (30 children) received conventional symptomatic therapy, including neurometabolic, cholinotropic drugs, classical massage and physiotherapy. In the study design, functional capacities and electromyographic data were estimated in a standardised time scheme with reference points («baseline», «1 year», «3 years», «5 years»).Results. The proposed methodology for clinical and electromyographic data sampling at different points of the disease progression has yielded results. We registered a weaker pathological progression in the main cohort reﬂected by less pronounced motor deﬁciency and electromyographic pathology compared to the comparison group receiving conventional symptomatic therapy.Conclusion. Dynamic monitoring of clinical and neurological disorders using modern assessment scales and extended electromyography of morbid motor markers enables a personalised proactive clinically justiﬁed treatment to suppress complications and manifestation of pathology.